CONCEPTUAL FRAMEWORK OF AGRICULTURAL INNOVATION POLICY IN AFRICAN COUNTRIES - Abdassalam Mnifid, Ali; Osama Mahmoud Ali, Mahmoud; Mohamed Abd Ahmed, Abuhteara; Omer Ali, Mohamoud (Ekonomija - teorija i praksa, 2022)
The aim of the paper is to present a conceptual framework from which to develop an appropriate innovation policy in African countries. Particular emphasis is placed on agricultural innovation, their role in stimulating agribusiness and the overall development of the African continent. Increasing food production and bioenergy, improving agricultural economics, African farmers' incomes, reducing poverty and adapting to climate change are challenges that can be addressed or mitigated by innovations in the agricultural sector. Africa's agriculture is a highly unproductive sector as a result of lack of appropriate innovative technologies, credit, infrastructure, lack of knowledge, information and skills. Agricultural innovations in African countries relate to the invention of insecticides, resistant varieties, fertilizers, irrigation pumps, genetic programs, sustainable agricultural practices, etc. Across Africa, farmers are embracing "climate-smart" innovations. An example of the response to climate change is the raising of 200 million new trees. African countries need to improve educational system performance, science and technology, institutions, increase financial and human investment to build local technology capabilities and learn from the experiences of other innovative regions. Although most African countries have made significant progress in terms of agricultural innovation, the results are still not quite satisfactory.